Proposed new interior design scheme of beauty centre for Mustika Ratu at Lengkuk Villa 2,Taman Taiping Villa, 34000 Taiping,Perak Darul Ridzuan / Ira Zaty Sofea Abd Kamal - Abd Kamal, Ira Zaty Sofea (Faculty of Architecture, Planning and Surveying, 2011)
The final project of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the purposed design.The project that had been chosen for the final project is to Proposed Interior Design Scheme Of Beauty Centre at Lenkuk Villa 2, Taman Taiping Villa, 34000 Taiping,Perak Darul Ridzuan. This proposed Beauty Centre for Mustika Ratu is to attract users,mostly on woman to try for themselves the treatment that the Mustika Ratu produce,at the same time to promote their product successfully as they offered a Javanese treatment and interiors,that comes mostly from Indonesia. The target market for the users of this Beauty Centre range product is woman, man, and teenager from all age and classes, that are concern about their look and appearances,not forgetting to find those who are interested in trying a javabased spa treatment. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself. Connected to that,the chosen design style for Mustika Ratu Spa is based on Javnese (contemporary) design,goes all the way I propose for client the traditional Javanese look and at the same time would attract the customers with different image that they would only get in Mustika Ratu. Statate into the design stage, that is vital to know the client needs such as type of services offered, products of the brand,spaces to be concluded in the proposed area,operation time, student also requirement to cafe studying to compare the advantage the disadvantage of the previous outlet.